Gema Perdamaian: Tourism, Religion and Peace in Multicultural Bali - Shinji Yamashita (Pusat Kajian Bali Universitas Udayana, 2012)
AbstractBalinese tourism has experienced serious challengesbecause of such negative incidents as the bombings bythe Muslim terrorists in the Balinese resort of Kuta in2002 and 2005. The inter-faith measures enacted as partof the crisis management for Balinese tourism after thebombings on 12 October 2002 are particularly interesting.These measures included joint- prayers to promote interreligiousharmony such as the prayer for world peace, DoaPerdamainan Dunia dari Bali (“Prayer for Peace of the Worldfrom Bali”) on 21 October 2002, which was attended bythe minister of religious affairs, who is himself Muslim. Inthis event the bombings were then interpreted by Balineseas an expression of the anger of gods, a consequence ofbad karma. Therefore, a massive ceremony, involving themost powerful priests, was carried out on 15 November2002 in order to cleanse Bali of the trauma of the bombingand restore peace. Since then the “prayer for peace” (GemaPerdamaian, literally “Echo of Peace”) has continued to beheld on 12 October every year. By focusing on this eventand the Balinese peace movement after the bombings,this paper discusses a new relationship between tourism,religion and peace within the framework of multiculturalBali in the age of transnationalism.